Pembuatan Mikrokristalin Selulosa Dari Batang Rumput Gajah (Pennisetum purpureum Schumach) - Zulharmitta Zulharmitta; Leza Viora; Harrizul Rivai (Jurnal Farmasi Higea, 2011)
Research about making of microcrystalline cellulose from stick bulrush ( Pennisetum purpureum Schumach) have done. From 300 g dry stick bulrush got 50,772 g microcrystalline cellulose. The loss on drying was about 5,57%. Characters a white, granular powder, odorless and tasteless. Identification with iodinated zinc chloride solution the substance becomes violet-blue. Solubility in the ammoniacal copper tetrammine solution it dissolves completely. Water-soluble substances the residue weighs is 0,085%. Starch with add iodine 0,05 M is negative (blue colour isn’t produced). The pH of the supernatan liquid is 5,46 and Hydration capacity is 3,504. Bulk and tapping densities is 0,251 and 0,374. Carr’s index and Hausner index  is 32,68 and 1,49. The inspection loss on drying, Characters organoleptic, Identification, Solubility in the ammoniacal copper tetrammine solution and Starch of result microcrystalline cellulose same with comparator (Vivacel pH 102) and fulfill conditions of British Parmacopoeia 2002.